Peran Koperasi Mahasiswa dalam Meningkatkan Kesejahteraan Anggota dan Implikasinya Terhadap Ketahanan Ekonomi Anggota (Studi Pada Kopma UIN Sunan Kalijaga Yogyakarta) - Zaim, Mohamad (Li Falah: Journal of Islamic Economics and Business, 2018)
This study examined the role of student cooperatives in improving member welfare and its implications on the economic resilience of members, by taking the object of research in Student Cooperation UIN Sunan Kalijaga Yogyakarta. The purpose of this study was to analyze the role of Student Cooperative "Kopma of Sunan Kalijaga State Islamic University" in improving the welfare of Student Cooperative Members "Kopma of Sunan Kalijaga State Islamic University" and it was implications for the Economic Resilience Member. To measure the indicators of economic resilience of members of student cooperatives in Student Cooperation UIN Sunan Kalijaga Yogyakarta used some indicators that are, 1) the income of entrepreneur members of the cooperative, 2) the fulfillment of basic needs. Some things which is done by student cooperatives in order to realize the economic resilience of members, 1) increasing the welfare of members of student cooperatives and 2) fulfillment of life needs through the business developed. However, there were still obstacles caused by members.This was due to loyalty and double roles by members in following cooperative activities.